Penguatan Personal Branding dan Peningkatan Penjualan Online Koperasi Preman Super Kecamatan Blimbing Kota Malang di Masa Pandemi Covid-19 - Leo Hutri Wicaksono; Tia Mulia Lailatul Nikmah; Triyanti Maulidiyah; Maria Febriyani Saveria Haghe (JURNAL APLIKASI DAN INOVASI IPTEKS "SOLIDITAS" (J-SOLID), 2021)
The Independent Women Source of Chage’s Cooperative better known as the Preman Super’s Cooperative is an association of women under the Preman Super’s Organization which was founded on March 21, 2021 in Malang City. The Preman Super’s Organization is an organization whose purpose is to eradicate poverty and empower women through the programs it runs. This Preman Super’s Cooperative has 70 active members, all of which are women entrepreneurs of MSMEs spread across its territory in Malang. The activities in the Preman Super’s Cooperative are Savings and Loan Cooperative services to help if MSME members are constrained by costs in their business and the Consumer Cooperative service to market the products of cooperative members through hotels, shops, and modern retail which is expected to have a wider reach. The problems found in the Preman Super’s Cooperative include: 1. There is still no logo and cooperative profile that has not yet been formed, 2. There is no E-Commerce account to promote products online, 3. Recording of financial statements is still manual. The impact of this activity is 1. The creation of a cooperative logo and profile for personal branding, 2. Increasing online sales of cooperative members through E-Commerce, 3. Assisting in the recording of financial reports online through an accounting application.